Storytelling sebagai Teknik Pembelajaran Bercerita bagi Siswa Sekolah Dasar - chaira salsabila; Dadi Satria (Universitas Negeri Surabaya, 2025)
Speaking ability is one of the important skills in learning Indonesian language at elementary school level. One effective method to develop this skill is storytelling technique. This study aims to analyze the effectiveness of storytelling as a learning method in improving elementary school students' speaking ability. The method used is a literature study with a qualitative descriptive approach, which is carried out by reviewing and synthesizing various scientific journals and relevant books. The results of the study indicate that storytelling makes a significant contribution to improving students' language skills, especially in the aspects of speaking, listening, and vocabulary mastery. In addition, storytelling has also been proven to increase students' learning motivation, self-confidence, and social-emotional abilities. This technique creates a fun, interactive, and inclusive learning atmosphere. Therefore, storytelling is recommended as a holistic and transformative learning strategy in Indonesian language education in elementary schools.